Strengths-Based Job Crafting and Employee Creativity: The Role of Job Self-Efficacy and Workplace Status - Yang, Zheng; Liu, Pingqing; Cui, Zunkang (Frontiers in Psychology, 2021)
While argued to be fostering creativity, the effect of job crafting on creativity often turned out to be less effective than expected. The reason is that most existing studies focused on the top-down job design interventions (Demerouti et al., 2015; Nielsen et al., 2010). We proposed an elaborated theoretical model to explain the influence of strengths-based job crafting on employee creativity. Specifically, we examined the mediating effect of job self-efficacy and the moderating effect of workplace status based on self-affirmation theory. A sample of 480 employees and their supervisors completed a battery of questionnaires. The results revealed that strengths-based job crafting was positively related to employee creativity, with job self-efficacy acting as a mediator for this relationship. Workplace status moderated both the direct and the indirect effects of job self-efficacy. For employees with a higher workplace status, strengths-based job crafting may generate more forces to promote employee creativity. The results suggest that strengths-based job crafting and workplace status can inspire employee creativity through a self-affirmation process.